Qualidade de vida em doenças pulmonares crônicas: aspectos conceituais e metodológicos - Ramos-cerqueira, Ana Teresa De Abreu [UNESP]; Crepaldi, André Luiz [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2000)
The present article purports to analyze aspects related to the concept of quality of life, taking into account the relevance of setting down parameters that allow for the evaluation of those aspects, especially in patients with chronic diseases. The analysis considered quality of life as one of the essential components of medical care, and pointed out the precautions that should be taken to choose instruments of evaluation, that should be sensitive and reliable to the dimensions they intend to evaluate.

O presente artigo teve por objetivo rever aspectos relativos ao conceito de qualidade de vida, tendo em vista a relevância de estabelecer parâmetros que permitam avaliar esse aspecto, especialmente em pacientes com doenças crônicas. Essa análise considerou a qualidade de vida como um dos componentes essenciais do cuidado médico e indicou as precauções a serem tomadas na escolha de instrumentos de avaliação, que devem ser sensíveis e fidedignos às dimensões que se pretende avaliar
Quality of life in chronic pulmonary diseases: conceptual and methodological aspects
Keywords: quality of life; chronic diseases; asthma; chronic obstructive pulmonary disease; qualidade de vida; doenças crônicas; asma; doença pulmonar obstrutiva crônica